Behavior, survival rate and histological alterations in Nile tilapia (Oreochromis niloticus-mossambicus) after exposed to abamectin - Thanomsit, Chutima; Ocharoen, Yhardpeth; Nanthanawat, Phochit (Asian Health, Science and Technology Reports, 2016)
Nile tilapia (Oreochromis niloticus-mossambicus) was applied to assess the toxicity of abamectin contamination in aquatic environment because it is normally found. It is classified as important protein source in many areas. In the case of being contaminated, it causes adverse effects in both fish health and human which is the top consumer. In this study, its toxicity was assessed based on behavior, survival rate and histological alterations in gill, liver, and intestine. The abamectin concentrations were 2.5, 5.0, 7.5 and 10 µg L-1 and exposure times at 24, 48, 72 and 96 h. After fish was exposed to abamectin, their behavior was changed that they swam without direction. Besides, their operculum frequently opened and closed. Then, they floated on surface of water and eventually died. In the concentration of 2.5 µg L-1 survival rate remained 100% until the end of experiment. For other concentrations, the rate decreased with an increasing in abamectin concentration and exposure time. The alterations observed in gill were hyperplasia, partial fusion of gill lamellae, edema and epithelial lifting. In the liver, cell was deformed and blood congestion, vacuolation and necrosis of hepatocyte were observed. And, lesion and necrosis in intestine of exposed fish were observed. Thus, it concluded that all alteration observed could be used as warning signal in other fish and Nile tilapia has a potential to be alternative bio-indicator for toxicant contamination in the waters.